Contemporary trends in the area of recruitment of employees as internal stakeholders of the organization - Bombiak, Edyta; Wereda, Wioletta (Management and Administration Journal, 2019)
In the era of increased competition for employees, and deepening the deficit of specialists in the labour market (brain drain) businesses are looking for new forms and tools of recruitment and their optimal compilation to win the most valuable specialists. Prospective employers must act quickly and be flexible; otherwise they lose valuable talents to other companies. This forces change in the approach to recruitment and results in the emergence of new forms and tools to attract valuable candidates, seen as internal stakeholders of the organization and encourages them to apply for a position.